Data Integrity Proofs in Document Management System under Cloud with Multiple Storage (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a web based computing which presents different customers an opportunity to store their data in the cloud. For cloud storage, privacy and security are the burning issues. Storing our data in cloud may not be fully trustworthy. When users store their data on the cloud then there may be a risk of losing the data, or sometimes data may be modified or updated. Cloud storage moves the user’s data to large data centers, which are remotely located, on which user does not have any control. One of the important concerns that need to be addressed is to assure the customer of the integrity i.e. correctness of his data in the cloud. As the data is physically not accessible to the user the cloud should provide a way for the user to check if the integrity of his data is maintained or is compromised. The aim of this paper is to ensure the integrity of the data and provides the proof that data is in secured manner and provide a  Cryptographic key to secure the data in the cloud